2006
DOI: 10.1111/j.2006.0908-8857.03825.x
|View full text |Cite
|
Sign up to set email alerts
|

Innate and learned aspects of vole urine UV‐reflectance use in the hunting behaviour of the common kestrel Falco tinnunculus

Abstract: Some birds are known to use the UV reflectance in their feeding strategy. Knowing that the common kestrel Falco tinnunculus is able to recognise vole trails by perceiving the UV reflectance of their scent marks, this study was designed to investigate whether the use of scent marks in the UV range has an innate component, or if it is only acquired with experience. We tested the preference of 44 experienced adult and 49 naïve juvenile common kestrels in four types of arenas: (1) scent‐marked and covered with a U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…With this new information, we used visual modelling to quantify the chromatic signals involved in two model systems of raptor-vole and raptor-songbird interactions. It has been suggested that UV signals have a predominant role in these interactions, either as cues for raptor hunting behaviour or as 'hidden' songbird signals concealed from raptors (Viitala et al, 1995;Håstad et al, 2005) (and see Zampiga et al, 2006;Zampiga et al, 2008). Our analyses show that raptors do not use UV cues for detection in these interactions, and our data suggest that it is unlikely that bank vole and field vole urine provide any visual cue that raptors can use.…”
Section: The Role Of Colour Vision In Raptor Huntingmentioning
confidence: 58%
“…With this new information, we used visual modelling to quantify the chromatic signals involved in two model systems of raptor-vole and raptor-songbird interactions. It has been suggested that UV signals have a predominant role in these interactions, either as cues for raptor hunting behaviour or as 'hidden' songbird signals concealed from raptors (Viitala et al, 1995;Håstad et al, 2005) (and see Zampiga et al, 2006;Zampiga et al, 2008). Our analyses show that raptors do not use UV cues for detection in these interactions, and our data suggest that it is unlikely that bank vole and field vole urine provide any visual cue that raptors can use.…”
Section: The Role Of Colour Vision In Raptor Huntingmentioning
confidence: 58%
“…The ontogenetic flexibility of foraging behaviour may vary considerably among even closely related species (e.g. [42,44]), but theoretically one would expect specialist foragers to have genetically fixed foraging techniques, and generalists to have flexible (learned) methods (cf. [42,45]).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been experimentally shown that birds can use UV cues in foraging. Diurnal avian predators are able to scan for potential hunting areas by using the scent markings of voles visible in UV light (Viitala et al 1995;Koivula and Korpimäki 2001;Zampiga et al 2006; but see Kellie et al 2004), but nocturnal owls probably cannot (Koivula et al 1997). In addition, redwings (Turdus iliacus) are attracted by UV-reflecting berries (Siitari et al 1999;Honkavaara et al 2004), and blue tits (Parus caeruleus) find cabbage moth larvae faster if the illumination includes UV light (Church et al 1998).…”
Section: Introductionmentioning
confidence: 98%